1994
DOI: 10.1093/clinchem/40.8.1575
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin binding to platelets in blood from patients with a sepsis syndrome

Abstract: Endotoxin, the lipopolysaccharide cell wall constituent of Gram-negative bacteria, produces symptoms of the Gram-negative sepsis syndrome. By measuring endotoxin in blood from septic patients it may be possible to select a subpopulation of patients in which mortality can be prevented by treatment with anti-endotoxin antibodies. We evaluated the performance of an endotoxin-free blood-collection tube. Within-run and between-run CVs of our endotoxin assay were 4-18% and 8-20%, respectively. In endotoxin-positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…Further work is required to determine whether the thrombin-induced expression of P-selectin on platelets or endothelial cells, followed by an increased binding of LPS to these cells, could have a significant role in the pathophysiology of organ failure in septic shock. It has been reported that in blood from sepsis patients most of the LPS is associated with activated platelets [4]. Our results indicate that LPS binding to activated platelets takes place via P-selectin and one function of LPS binding to platelets could be to remove soluble LPS from blood.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Further work is required to determine whether the thrombin-induced expression of P-selectin on platelets or endothelial cells, followed by an increased binding of LPS to these cells, could have a significant role in the pathophysiology of organ failure in septic shock. It has been reported that in blood from sepsis patients most of the LPS is associated with activated platelets [4]. Our results indicate that LPS binding to activated platelets takes place via P-selectin and one function of LPS binding to platelets could be to remove soluble LPS from blood.…”
Section: Discussionmentioning
confidence: 53%
“…Activated platelets play a major role in DIC. Rat models of septic shock and LPS-induced liver injury have shown that an accumulation of platelets, followed by neutrophil infiltration, contribute to the manifestation of LPSinduced tissue damage [2][3][4]. Several lines of evidence indicate that thrombin is required for LPS-mediated organ failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because both humans and horses are exquisitely susceptible to endotoxin, there has long been a strong desire to quantify systemic endotoxemia in an effort to better understand its role in these disease processes and as a predictor of mortality. However, measurement of endotoxin in the systemic circulation has been complicated by the fact that endotoxin binds to platelets, and RBCs interfere with the commonly used chromogenic Limulus amebocyte lysate assay 5–7 Consequently, the platelet‐rich plasma (PRP) fraction of whole blood (WB) is the desirable sample fraction needed for an accurate determination of systemic endotoxin. In addition to platelet‐binding, the anticoagulant used can substantially influence results.…”
mentioning
confidence: 99%
“…In addition to platelet‐binding, the anticoagulant used can substantially influence results. Specifically, heparin, the anticoagulant commonly used in equine plasma‐based clinical pathologic research, causes platelet activation and aggregation, modulates activated polymorphonuclear leukocyte‐induced platelet activation, and binds to both cell types, as does endotoxin 5,8–10 . Thus, heparin‐medi‐ated actions may directly or indirectly affect endotoxin quantification 11 .…”
mentioning
confidence: 99%